Recovery profiles following single and multiple matches per week in professional football. Issue 10 (26th November 2019) - Howle, Kieran; Waterson, Adam; Duffield, Rob
Abstract: Objectives: To investigate player responses 48 h post single (SM) and multi-match (MM) weeks on two subjective and three objective outcome measures to infer recovery status.Methods: From 42 professional players over 2 seasons, outcome measures relevant to recovery status were collected 48 h following matches, as well as during pre-season training weeks as a comparative baseline. These included (1) 5-item subjective wellness questionnaire, (2) total quality recovery (TQR) scale, (3) hip adduction squeeze test, ankle knee to wall (KTW) test, and active knee extension (AKE) flexibility test. These outcome measures 48 h post-match were compared for SM ( n  = 79) and MM ( n  = 86) weeks where players completed >75 min of match time in only one (SM) or if both matches were played and had <96 h recovery (MM). Internal match load was collected from each match based on session rating of perceived exertion (sRPE) multiplied by match duration.Results: Subjective wellness (specifically fatigue, sleep and soreness), TQR and hip adduction squeeze test were all significantly reduced following match 1 at 48 h post for both SM and MM ( p  < 0.05), and further reduced following match 2 in MM ( p  < 0.05). No other outcome measures to infer recovery showed significant differences ( p  > 0.05) within or between-conditions.Conclusions: Subjective wellness, TQR and hip adduction strength showed reduction 48 h post match for players competing in multiple matches with <96 h recovery. Therefore, these outcome measures may be of use to practitioners to assess readiness to compete during congested competition schedules.